Exploring Empathy in The Human Development Perspective and Its Practical Implications Based on The Islamic Foundations - Popi Rosepti (Universitas Teuku Umar, 2023)
This study aims to figure out the concept of empathy based on human development perspective and find its practical implication in the Islamic teaching, stated in its fundamental foundations, the Quran and hadiths. The exploration of the issue is based on the purpose to analyze the nature of empathy in human development and to provide a source regarding its implication based on Islamic view. Since the values are presumably derived from humanistic psychology (general knowledge), this study also explores the concept that is linked to the value in Islamic traditions. Descriptive qualitative research using a library study is employed to explore both concepts together with a content analysis for its data representation. The finding shows empathy is primed since infancy and continuously develops following the maturity of each stage of life. They develop similar emotion and process of it but different ways in showing their empathetic behaviors. Connecting to the implication in the Islamic teaching, there are 16 points elaborating the concept of empathy; five from the Quran and 11 from hadiths. Most of them are described in various ways of teaching but still closely relate to human social interaction. The result of this study reveals that both psychology and Islam are similar in defining empathy as a universal value in human life which drives people to the ability of understanding others’ feeling and being compassionate on it.